Efek Stimulansia Infus Lada Hitam (Piperis nigri fructus) Pada Mencit - ROS SUMARNY; LESTARI RAHAYU; NI MADE DWI SANDHIUTAMI; LIBERT MORY (Fakultas Farmasi Universitas Pancasila, 2013)
Black pepper (Piperis nigri fructus) has been empirically used to eliminate fatigue and to increase stamina or as stimulant. The aim of this study was to determine the efficacy of black pepper infuse as stimulant on 30 male DDY mice using swimming and rotarod methods. The mice were divided into five groups. First group was given distilled water as control, second group was given caffeine of 0.36 mg/20 g bw. The other three groups were given orally with black pepper infuse of 0.32 mg/20 g bw, 0.65 mg/20 g bw, or 1.3 mg/20 g bw. Observations on mice swimming endurance and mice endurance on a rotarod, were carried out 60 minutes after oral administration of the solutions. Analysis using Kruskal-Wallis showed that there was significant difference in the stimulant efficacy between the black pepper infuse and the negative control (p<0.05). There was no significant difference in stimulant effect between the 0.32 mg/20 g bw of black pepper infuse and the caffeine positive control, however, the infuse dose of 0.65 mg/20 g bw and 1.3 mg/20 g bw have demonstrated stronger stimulant effects (p>0.05) as compared to the caffeine positive control.